Gastrointestinal Bleeding in Antithrombotic Therapy in Patients with Coronary Heart Disease: Risk Factors, Pathogenesis and Treatment - N. S. Lapina; A. A. Alekseeva; A. D. Vershinina; N. S. Khruleva; F. N. Muradova; L. Y. Koroleva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Description of risk factors, pathogenesis and treatment strategies of gastrointestinal bleeding (GIB) in the course of antithrombotic therapy in patients with coronary heart disease (CHD).Key points. Risk factors of GIB during antithrombotic therapy in CHD patients include: GIB, gastric and/or duodenal ulcer in the history, reflux esophagitis, presence of H. pylori, inflammatory bowel disease, diverticula, haemorrhoids, angiodysplasia, gastrointestinal neoplasia, age above 65 years, concomitant treatment with non-steroidal anti-inflammatory drugs (NSAIDs), glomerular filtration rate <50 mL/min, high doses of direct oral anticoagulants (DOACs) ≥3 in HAS-BLED score. Pathogenesis of GIB in the course of antithrombotic therapy is associated with systemic hypocoagulation and local damaging effects of these drugs. Strategies of GIB treatment during DOAC therapy in patients with CHD are determined by severity of bleeding and threat to life. Aside to standard conservative measures, endoscopic or surgical haemostasis requires usage of antidotes to suppress effects of DOACs and other specific drugs in severe cases.Conclusion. GIB associated with antithrombotic therapy in CHD patients poses a serious medical problem of growing importance with wider application of anticoagulant drugs. Antithrombotic therapy requires accurate decision making, risk assessment, careful monitoring of the patient’s condition and timely diagnosis of gastrointestinal disorders following good rationale in GIB prevention.